Highlights from the 2023 International Meeting on the Molecular Biology of Hepatitis B virus - Allweiss, Lena; Cohen, Chari; Dias, Joao; Fumagalli, Valeria; Guo, Haitao; Harris, James M; Hu, Jianming; Iannacone, Matteo; Isogawa, Masanori; Jeng, Wen-Juei; Kim, Kyun-Hwan; Kramvis, Anna; et al. (Journal of general virology, 2024)
Since its discovery in 1965, our understanding of the hepatitis B virus (HBV) replication cycle and host immune responses has increased markedly. In contrast, our knowledge of the molecular biology of hepatitis delta virus (HDV), which is associated with more severe liver disease, is less well understood. Despite the progress made, critical gaps remain in our knowledge of HBV and HDV replication and the mechanisms underlying viral persistence and evasion of host immunity. The International HBV Meeting is the leading annual scientific meeting for presenting the latest advances in HBV and HDV molecular virology, immunology, and epidemiology. In 2023, the annual scientific meeting was held in Kobe, Japan and this review summarises some of the advances presented at the Meeting and lists gaps in our knowledge that may facilitate the development of new therapies.